Improving Resource Access Processes in Protected Areas - CARE International in Uganda (Uganda Wildlife Society, 2004)
National Parks in Uganda provide essential goods and services to both rural and urban populations, such as craft materials, herbal medicine, water, fuel wood, fodder, timber and ecological functions like soil erosion control and improvement of soil fertility. As a result, the ecological integrity of national parks in Uganda influences the rate at which various sections of the society in the country can meet poverty reduction goals.